Pathogenesis of Corynebacterium diphtheriae and available vaccines: An Overview - Syed Babar Jamal; Sandeep Tiwari; Artur Silva; Vasco Azevedo (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2017)
Corynebacterium diphtheriae is Gram-positive bacteria responsible for causing diphtheria in human and once regarded for high mortalities worldwide. The fatality gradually decreased with improved living standards and further alleviated when many immunization programs were introduced. Public infectious diseases have positively been controlled by vaccination, yet, the importance of vaccination usually remained unnoticed for the adults. Many of the under-development vaccines are directed towards the childhood immunization. However, numerous drug-resistant strains emerged recently that consequently decreased the effi ciency of current therapeutics and vaccines, thereby obliging the scientifi c community to start investigating new therapeutic targets in pathogenic microorganisms. In this study, we try to put together a short information regarding pathogenesis of Corynebacterium diphtheriae and reported vaccine till the date. Furthermore, we highlighted the emerging technique for identifi cation of new therapeutic targets.